2016
DOI: 10.1016/j.nimb.2016.03.015
|View full text |Cite
|
Sign up to set email alerts
|

H+-induced irradiation damage resistance in Fe- and Ni-based metallic glass

Abstract: In this study, use of 40-keV H + ion for irradiating metallic glass Fe80Si7.43B12.57 and Ni62Ta38 as well as metallic tungsten (W) at fluences of 1 × 10 18 and 3 × 10 18 ions/cm 2 , respectively, was investigated. At the fluence of 1 × 10 18 ions/cm 2 , a crystalline layer appeared in metallic glass Fe80Si7.43B12.57, with -Fe as the major crystalline phase, coupled with a little Fe2B, Fe3B, and metastable β-Mn-type phase. Fe80Si7.43B12.57 exhibited good soft magnetic properties after irradiation. At the fluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
2
2
0
1
Order By: Relevance
“…For example, similar surface smoothening was reported in [53,54]. Moreover, surface roughening was found in other investigations [55,56] and attributed to the damage induced under ion irradiation in different metallic glasses.…”
Section: Surface Morphology Evolutionsupporting
confidence: 86%
“…For example, similar surface smoothening was reported in [53,54]. Moreover, surface roughening was found in other investigations [55,56] and attributed to the damage induced under ion irradiation in different metallic glasses.…”
Section: Surface Morphology Evolutionsupporting
confidence: 86%
“…The observed phenomenon of connection and growth of helium bubbles is consistent with the result of Fig.9 that the large bubbles formed. In our previous studies, similar growth of bubbles had been observed in Zr-based metallic glass under 500 keV He 2+ ion irradiation [20] and Fe-based metallic glass irradiated by 40 keV proton [9]. Fig.10(d) shows the HRTEM image of crystallization in helium bubble layer of metallic glass Fe80Si7.43B12.57.…”
Section: Evolution Of Fe 80 Si 743 B 1257 Metallic Glass Microstrucsupporting
confidence: 75%
“…The samples were irradiated with He 2+ ions of 300keV energy with fluences of 1×10 17 ions/cm 2 , 2×10 17 ions/cm 2 , 4×10 17 ions/cm 2 , 1×10 18 ions/cm 2 and 1.6×10 18 ions/cm 2 . To avoid the effect of irradiation ions flux on the material behavior [9,10], the flux for all the samples was 1.2×10 13 ions/cm 2 s.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In addition, SAM2X5 amorphous coatings are being used as corrosion-resistant anti-skid decking for ships. No significant irradiation damage phenomena appear in the Fe 80 Si 7.43 B 12.57 metallic glass, while blistering, flaking, and other damage occurs on the surface of the metallic W in an environment subjected to H + irradiation [3]. The Fe-based amorphous coating with the composition of Fe 54.2 Cr 18.3 Mo 13.7 Mn 2 W 6 B 3.3 C 1.1 Si 1.4 (wt.%) used on marine pump impellers has an erosion rate that is two to three times that of SUS304, and it is believed to enhance the lifetime of pump impellers that need to work in sand-containing seawater [4].…”
Section: Introductionmentioning
confidence: 98%